2020
DOI: 10.18632/oncotarget.27712
|View full text |Cite
|
Sign up to set email alerts
|

Down syndrome iPSC model: endothelial perspective on tumor development

Abstract: Trisomy 21 (T21), known as Down syndrome (DS), is a widely studied chromosomal abnormality. Previous studies have shown that DS individuals have a unique cancer profile. While exhibiting low solid tumor prevalence, DS patients are at risk for hematologic cancers, such as acute megakaryocytic leukemia and acute lymphoblastic leukemia. We speculated that endothelial cells are active players in this clinical background. To this end, we hypothesized that impaired DS endothelial development and functionality, impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 79 publications
(88 reference statements)
1
2
0
1
Order By: Relevance
“…In addition, abnormal cell adhesion was also found in the bioinformatics analysis of other DS hiPSCs (Hibaoui et al, 2014 ; Gonzales et al, 2018 ). These results are consistent with the other studies, in which the RNA-seq are used as the major research platform (Hibaoui et al, 2014 ; Gonzales et al, 2018 ; Perepitchka et al, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, abnormal cell adhesion was also found in the bioinformatics analysis of other DS hiPSCs (Hibaoui et al, 2014 ; Gonzales et al, 2018 ). These results are consistent with the other studies, in which the RNA-seq are used as the major research platform (Hibaoui et al, 2014 ; Gonzales et al, 2018 ; Perepitchka et al, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…They also found that trisomy 21 enhanced the proliferative phenotype, reproducing the cellular and molecular abnormalities in DSassociated AMKL. Galat et al (2020) showed DS iPSC-derived progenitor stromal cells had aberrant musculoskeletal development and resistance to solid tumors. Additionally, Perepitchka et al (2020) found that DS iPSC-derived endothelial cells exhibited decreased proliferation, migration, and inflammatory response.…”
Section: Insights On Ds-associated Leukemogenesis and Solid Tumor Res...mentioning
confidence: 99%
“…Galat et al (2020) showed DS iPSC-derived progenitor stromal cells had aberrant musculoskeletal development and resistance to solid tumors. Additionally, Perepitchka et al (2020) found that DS iPSC-derived endothelial cells exhibited decreased proliferation, migration, and inflammatory response. They also reported a set of genes potentially associated with the unfavorable solid tumor microenvironment and with the elevated leukemia risk in DS, suggesting that these genes could be potential therapeutic targets in translational cancer research (Perepitchka et al, 2020).…”
Section: Insights On Ds-associated Leukemogenesis and Solid Tumor Res...mentioning
confidence: 99%
“…Não se sabe ainda o porquê dessa prevalência, apesar de alguns estudos apontarem que as células endoteliais de pacientes com SD poderiam ser a chave para a explicação 10 . Mas é fato a importância de um acompanhamento do paciente desde o seu primeiro dia de vida [11][12][13] .…”
Section: Introductionunclassified